ANALYSIS OF RICE CRACKER RAW MATERIAL INVENTORY CONTROL WITH THE ECONOMIC ORDER QUANTITY (EOQ) METHOD AT UMKM RANGGINANG RIZAL PEOPLE'S TASTES IN CIJAMBE VILLAGE - JOJO JOJO; Farida Farida (JABI (Journal of Accounting and Business Issues), 2025)
This study aims to analyze the control of glutinous rice raw material inventory at UMKM Ranginang Rizal People’s Taste in Cijambe Village using the Economic Order Quantity (EOQ) method. The main problems faced by the UMKM include limited capital, simple inventory management, and high inventory costs due to conventional ordering policies. The research employed a descriptive qualitative approach combined with quantitative analysis using EOQ calculations based on procurement and usage data of raw materials in 2024. The findings show that the conventional method applied by the UMKM generated a total inventory cost of IDR 12,030,000 per year, while the EOQ method required only IDR 1,200,000 per year. Furthermore, EOQ determined an optimal order quantity of 4,000 kg with one order per year, a safety stock of 199 kg, and a reorder point of 200 kg. Therefore, implementing EOQ significantly improves inventory control efficiency and reduces annual costs